Semi Field Trial Competitive Power Married Made Sterile Aedes Albopictus as Method of Vector Control: A Current Vector Controlling Method - Rosyadi, Ahmad; Sehabudin, Ahmad; Rifayat, Ariel (Journal of Ultimate Public Health, 2019)
Aedes albopictus is a plant that causes Dengue Hemorrhagic Fever is not as prevalent as Aedes Aegypti is not a disease given by Aedes albopictus mosquito is not much different from Aedes Aegypti mosquito. The Case Fatality Rate (CFR) of Dengue Fever is very high in Indonesia, at 41.4% at the beginning of dengue cases in Indonesia. Innovation continues to create for disease vector control to break the chain of disease. The use of sterile insect techniques is a useful thing in the things that need to be socialized in the community.